2013
DOI: 10.1073/pnas.1312637110
|View full text |Cite
|
Sign up to set email alerts
|

KpsC and KpsS are retaining 3-deoxy- d - manno -oct-2-ulosonic acid (Kdo) transferases involved in synthesis of bacterial capsules

Abstract: Significance Capsules are bacterial surface structures used by many Gram-negative pathogens to evade the host immune system. They are comprised of long carbohydrate chains, called capsular polysaccharides (CPSs), which possess a lipid at one end. The lipid is connected to the CPS through an unusual linker consisting of five to nine residues of an acidic sugar 3-deoxy- d - manno -oct-2-ulosonic acid (Kdo). This study identifies two conserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
94
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 46 publications
1
94
0
Order By: Relevance
“…From the genes flanking acs operons, cmcAX, ccpAX, bglxA, bcsX, and bcsY have been previously shown to contribute to cellulose production in closely related species (26,33,34). We found two other, stand-alone copies of bglxA from the genome (genomic positions 517401-519440 and 3029825-3032221), and also identified genes close to acs2 that are associated with extracellular matrix formation (kpsC, kpsS, and rfaB) and may play a role in cellulose productivity (35,36). Finally, to determine whether the iGEM strain can fix atmospheric nitrogen similar to G. diazotrophicus, we searched its genome for genes associated with nitrogen fixation.…”
Section: Resultsmentioning
confidence: 74%
“…From the genes flanking acs operons, cmcAX, ccpAX, bglxA, bcsX, and bcsY have been previously shown to contribute to cellulose production in closely related species (26,33,34). We found two other, stand-alone copies of bglxA from the genome (genomic positions 517401-519440 and 3029825-3032221), and also identified genes close to acs2 that are associated with extracellular matrix formation (kpsC, kpsS, and rfaB) and may play a role in cellulose productivity (35,36). Finally, to determine whether the iGEM strain can fix atmospheric nitrogen similar to G. diazotrophicus, we searched its genome for genes associated with nitrogen fixation.…”
Section: Resultsmentioning
confidence: 74%
“…Other investigators have suggested that the altered stoichiometry of LipA/KpsC to other capsule biosynthetic components may result in aberrant capsule chain length (21), raising the possibility that altered stoichiometry of capsule synthesis components through complementation at a nonnative locus may result in a similar change in capsule chain length. As another approach to quantify the amount of polysaccharide in the mutant and complemented strains, we measured thiobarbituric acid (TBA) reactivity.…”
Section: Capsule Biosynthesis Genes Are Not Restricted To a Single Lomentioning
confidence: 99%
“…Some organisms use Kdo (3-deoxy-D-manno-oct-2-ulosonic acid) residues as a link between the lipid and the sugar polymer (62). The KpsC and KpsS GTs were recently shown to catalyze this reaction (115). E. coli K1 CPS biosynthesis involves a NeuS polysialyltransferase and a NeuE accessory protein (116).…”
Section: Cell Wall Polysaccharides: Capsular Polysaccharides and Exopmentioning
confidence: 99%